A Regulatory Sandbox for Robo Advice - Wolf-Georg Ringe; Christopher Ruof (University of Hamburg, Institute of Law and Economics (ILE), 2018)
Robo advice, the automated provision of financial advice without human intervention, holds the promise of cheap, convenient and fast investment services for consumers – freed from human error or bias. However, retail investors have limited capacity to assess the soundness of the advice, and are prone to make hasty, unverified investment decisions. Moreover, financial advice based on rough and broad classifications may fail to take into account the individual preferences and needs of the investor. On a more general scale, robo advice may be a source of new systemic risk. At this stage, the existing EU regulatory framework is of little help. Instead, this paper proposes a regulatory "sandbox" – an experimentation space – as a step towards a regulatory environment where such new business models can thrive. A sandbox would allow market participants to test robo advice services in the real market, with real consumers, but under close scrutiny of the supervisor. The benefit of such an approach is that it fuels the development of new business practices and reduces the "time to market" cycle of financial innovation while simultaneously safeguarding consumer protection. At the same time, a sandbox allows for mutual learning in a field concerning a little-known phenomenon, both for firms and for the regulator. This would help reducing the prevalent regulatory uncertainty for all market participants. In the particular EU legal framework with various layers of legal instruments, the implementation of such a sandbox is not straightforward. In this paper, we propose a "guided sandbox", operated by the EU Member States, but with endorsement, support, and monitoring by EU institutions. This innovative approach would be somewhat unchartered territory for the EU, and thereby also contribute to the future development of EU financial market governance.
Keywords: 330